Green synthesis of magnetic nanoparticles using leaf extracts of Aloe vera and Kalanchoe daigremontiana to remove divalent mercury from natural waters (2019)
In this study, magnetic nanoparticles of magnetite were prepared by an eco-friendly method using aqueous leaf extracts of Aloe vera and Kalanchoe daigremontiana. These vegetal extracts have suitable characteristics such as high availability, low cost, and serve as good colloidal stabilizers. Synthetized products were characterized by Transmission Electron Microscopy (TEM), Room Temperature Mossbauer Spectroscopy (RT-MS), and their potential use as adsorbents for Hg (II) removal in natural waters was evaluated by Atomic Absorption Spectroscopy (AAS). Size distribution and morphology of the products obtained by TEM show spherical nanoparticles composites, with sizes between 3 and 10 nm for both extracts. Mossbauer spectra are consistent with superparamagnetic particles for both samples. Moreover, particles from both extracts showed mercury removal efficiencies above 75%. © Published under licence by IOP Publishing Ltd.